Immunohistochemical Analysis of CYP11B2, CYP11B1 and β-catenin Helps Subtyping and Relates With Clinical Characteristics of Unilateral Primary Aldosteronism - Sun, Luyan; Jiang, Yiran; Xie, Jing; Zhu, Hongyuan; Wu, Luming; Zhong, Xu; Zhou, Weiwei; Su, Tingwei; Wang, Weiqing (Frontiers in Molecular Biosciences, 2021)
Background: Primary aldosteronism is caused by aldosterone overproduction. While conventional hematoxylin-eosin staining can demonstrate morphological abnormality, it cannot provide any functional histopathological information. We aimed to identify the diagnostic, functional and prognostic value of CYP11B2, CYP11B1, and β-catenin immunostaining in unilateral hyperaldosteronism. Method: A total of 134 patients with unilateral hyperaldosteronism were recruited in our study. The expression of CYP11B2, CYP11B1 and β-catenin was evaluated semiquantitatively on 134 patients’ sections using immunohistochemistry technology and the relationship with clinical data was assessed. Results: Patients were classified into four subtypes based on CYP11B2 staining as below: (1)118 patients with unilateral single aldosterone-producing adenoma (APA), (2)11 with unilateral multiple APA, (3)four with aldosterone-producing cell cluster (APCC), and (4)one with an undefined source. Adjusted CYP11B2 H-score was correlated with serum aldosterone, aldosterone to renin ratio (ARR), and serum potassium. In the abnormal β-catenin staining group, hypertension duration, aldosterone, ARR, cortisol, tumor diameter, tumor area, and CYP11B2 H-score were significantly higher than those of the wild-type group. Serum potassium level was significantly lower in the abnormal β-catenin staining group. Age, gender, BMI, family history of hypertension, adjusted CYP11B2 and CYP11B1 H-scores differed significantly between complete clinical success and incomplete clinical success groups. Age, gender and family history of hypertension were independently associated with complete clinical success based on multivariate logistic regression analysis. Conclusion: CYP11B2 immunostaining could improve the differential diagnosis of unilateral hyperaldosteronism. Adjusted CYP11B2 H-score could be used as a histopathological marker to reflect the severity of unilateral APA. Dysregulation of Wnt/β-catenin signaling and impaired β-catenin degradation may provoke the proliferation and enhance the steroidogenic ability of APA tumor cells, indicating that the Wnt pathway might be a potential, actionable, therapeutic target in the treatment of hyperaldosteronism. Age, sex and family history of hypertension were independent predictors of clinical outcome after adrenalectomy for unilateral hyperaldosteronism.